2020
DOI: 10.1042/cs20191020
|View full text |Cite
|
Sign up to set email alerts
|

Factor XII blockade inhibits aortic dilatation in angiotensin II-infused apolipoprotein E-deficient mice

Abstract: Abdominal aortic aneurysm (AAA) is an important cause of mortality in older adults. Chronic inflammation and excessive matrix remodelling are considered important in AAA pathogenesis. Kinins are bioactive peptides important in regulating inflammation. Stimulation of the kinin B2 receptor has been previously reported to promote AAA development and rupture in a mouse model. The endogenous B2 receptor agonist, bradykinin, is generated from the kallikrein–kinin system following activation of plasma kallikrein by F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Moreover, PTPN22 showed interactions with 20 proteins/genes (Fig. S4e), among which 3 molecules have been reported to be important in AAA progress including PRKCD, EGFR, and PDGFRB [28][29][30]. Collective, these data highlight the important role of immune response and Garcinia acid as a potential therapeutic drugs for AAA.…”
Section: Lilrb2 and Ptpn22 Have No Diagnostic Value For Taa Patientsmentioning
confidence: 85%
“…Moreover, PTPN22 showed interactions with 20 proteins/genes (Fig. S4e), among which 3 molecules have been reported to be important in AAA progress including PRKCD, EGFR, and PDGFRB [28][29][30]. Collective, these data highlight the important role of immune response and Garcinia acid as a potential therapeutic drugs for AAA.…”
Section: Lilrb2 and Ptpn22 Have No Diagnostic Value For Taa Patientsmentioning
confidence: 85%
“…Upon histological examination of collagen deposition within AAAs, an indicator of structural stability, we observed a thick, fibrous layer of collagen deposited at the IMT–vessel interface in animals treated with 3F7. Recently, a study by Moran et al 32 investigated the gene and protein profiles of both an ApoE −/− FXII −/− double-knockout and an ApoE −/− 3F7-treated mouse model. The authors reported decreases in ADAM-17, endothelial growth factor receptor, and the matrix metalloproteinases MMP-2 and MMP-9 expression, 32 correlating to reduced local inflammation and remodeling, as well as to the preservation of extracellular matrix integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Both ultrasound and morphometric measurements have been found to have excellent inter-observer reproducibility in the investigators prior studies [11,14,15].…”
Section: Assessment Of Aaa Severitymentioning
confidence: 93%
“…Maximum SRA diameter was measured using ultrasound as previously reported [14]. In study 2, the ultrasound was performed before the diet was introduced (baseline), before AngII infusion (day 0), and at day 14 and 28 after the AngII infusion was commenced.…”
Section: Assessment Of Aaa Severitymentioning
confidence: 99%
See 1 more Smart Citation